Are living beings extended autopoietic systems? An embodied reply. (February 2020) - Villalobos, Mario; Razeto-Barry, Pablo
Building on the original formulation of the autopoietic theory (AT), extended enactivism argues that living beings are autopoietic systems that extend beyond the spatial boundaries of the organism. In this article, we argue that extended enactivism, despite having some basis in AT's original formulation, mistakes AT's definition of living beings as autopoietic entities. We offer, as a reply to this interpretation, a more embodied reformulation of autopoiesis, which we think is necessary to counterbalance the (excessively) disembodied spirit of AT's original formulation. The article aims to clarify and correct what we take to be a misinterpretation of AT as a research program. AT, contrary to what some enactivists seem to believe, did not (and does not) intend to motivate an extended conception of living beings. AT's primary purpose, we argue, was (and is) to provide a universal individuation criterion for living beings, these understood as discrete bodies that are embedded in, but not constituted by, the environment that surrounds them. However, by giving a more explicitly embodied definition of living beings, AT can rectify and accommodate, so we argue, the enactive extended interpretation of autopoiesis, showing that although living beings do not extend beyond their boundaries as autopoietic unities, they do form part, in normal conditions, of broader autopoietic systems that include the environment.